Prosopis sp. tree-ring oxygen and carbon isotope record of regional-scale hydroclimate variability during the last 9500 years in the Atacama Desert - Olson, E. J.; Dodd, J. P.; Rivera, M. A. (My University, 2020)
The hyper-arid core of the Atacama Desert is one of the most persistently arid environments in the world, yet there is evidence of significant hydroclimate variability during the Holocene. The timing of regional scale pluvial or humid periods has important implications for understanding the drivers of South American climate variability as well as the development of agriculture by prehistoric cultures. Here we present oxygen (delta O-18) and carbon (delta C-13) isotope values from ancient Prosopis sp. tree-ring cellulose as a record relative humidity (RH) and water availability (via intrinsic water-use efficiency) over century-long intervals throughout the past 9.5 ka in the northern Atacama Desert (19-21 degrees S). These data provide the first high-resolution (ca. annual) evidence for decreasing water availability and increasing climate variability in the Atacama from the early-to late- Holocene. Intrinsic water-use efficiency steadily increases over the Holocene indicating a lowering of the water table and a reduction in the availability of groundwater resources in the region. As water availability decreases, delta O-18-based estimates of RH show increased variance beginning similar to 4.9 ka. This change in RH coincides with the onset of modern day Central Andean atmospheric circulation patterns and previously documented humid periods in the southern Altiplano (22-24 degrees S). Subannual tree-ring isotope analysis of modern and early Holocene (8.3 ka) trees show a similar seasonal cycle in carbon isotope values that correlates with modern annual changes in temperature; however, the early Holocene interseasonal variability is greater than modern seasonality. delta O-18 values of the Atacama tree-rings are highly correlated with those of the Sajama ice core from the Bolivian Andes, demonstrating a teleconnection between high-altitude Andean precipitation and water availability in the Atacama Desert. These reconstructions together provide a record of Holocene water availability and ephemeral recharge related to changes in ENSO and South American monsoon.
Keywords: climate; holocene; early agriculture; enso; andes; south america